TOPIKALISASI SEBAGAI SARANA MEMAHAMI ISI WACANA SERAT SANA SUNU - Avi Meilawati (JURNAL IKADBUDI, 2013)
This research aims to describe the topics in the ninth chapter of Serat Sana Sunu, how the topicalization and what topics which build the discoure. It  consists of 34 stanza The theme on chapter IX focuses on how to say politely. The data collects by reading and noting. The data analyzing by finding the topiks from each stanza, each sentence, and word. The second step is describing the data through the descriptive way. There are two types of topicalitation. First, the author describes the topic full in one paragraph. Second, the topic separate in many paragraps. The starting topic is not only in the first line each paragraph, but also in the middle or in the last line. There are two big theme in the chapter; the seven talking interdiction and the polite way to say in many conditions. The seven interdictions are lie, gossip, say something bad about someone else, arrogant, say jokingly, conceited, and say something unuseful. The other commands are to say in polite way to brother, sister; politeness as a servant, and the way to say in a meeting or forum. The rules in chapter IX from Serat Sana Sunu can be used as a reminder to be polite. It also can be an alternative way to solve the young generation problem to say in a better way. Keywords: topic, Serat Sana Sunu